Synthesis and binding affinities of 2 beta-(3-iodoallyloxycarbonyl)3 beta-(4-substituted-aryl)tropane analogues as ligands for the dopamine transporter studies - Chung, KH; Lim, CH; Lee, DR; Jin, CB; Chi, DY (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
Tropane analogues from cocaine, which is known to be one of the most reinforcing and addictive compounds, were designed, synthesized, and characterized for inhibition of presynaptic uptake of dopamine (DA) in brain. Eight new derivatives of 3 beta -aryl-2 beta-(3-iodoallyloxycarbonyl)tropanes were synthesized and tested for their potential abilities to displace [H-3]2 beta -carbomethoxy-3 beta-(4-fluorophenyl)tropane (WIN 35,428) binding to the rat striatal membranes. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: POSITRON EMISSION TOMOGRAPHY; CENTRAL NERVOUS-SYSTEM; PARKINSONS-DISEASE; IMAGING AGENTS; COCAINE; ESTERS; <TC-99M>TRODAT-1; INHIBITION; CHEMISTRY; PROVIDES